(Des)construção de gestores-celebridades brasileiros: histórias midiáticas do management nacional e regional - Santana, Karine de Jesus Rodrigues (2023)
Celebrities constitute an aspect of mass culture, emerging from the cultural commodification processes as a product of the actions of agents and organizations that make up the so-called cultural industry. With the diffusion of electronic media and the worldwide computer network, there is the emergence of digital influencers. The virtual space becomes one of the components of celebrities’ actions and a field for regional and local celebrity managers to expand their business activities. This thesis focuses on the representation of celebrity managers and the act of being represented by them, and it is guided by the identification of how the construction and deconstruction of celebrity managers occur. The structure of the text comprises two empirical chapters, which aim to analyze the processes of construction and deconstruction of celebrity managers. In the theoretical field, the study was based on social science studies on celebrities and mass culture - Celebrity Studies, and on studies on business celebrities. Specifically, the first empirical chapter, corresponding to the second in the linear sequence of this thesis, analyzes the processes of construction and deconstruction of a national-international celebrity manager, through the discussion of the rise and fall of Eike Batista. The second empirical chapter, corresponding to the third in the linear sequence of this thesis, investigates how regionalism is present in the construction process of local-regional entrepreneurial-celebrities, through the research of entrepreneurial celebrities in the fashion industry in the Triângulo Mineiro region (State of Minas Gerais) and southern State of Goiás. Regarding the epistemic methodological definitions, in the first empirical chapter, a post-structuralist perspective was used with the application of the concept of deconstruction to assess media reports (newspapers, magazines, videos, and books) about the celebrity manager Eike Batista. In the second empirical chapter, a post-structuralist perspective of feminist studies was used to analyze the material collected from documentary research and interviews with eight regional-local fashion entrepreneurial celebrities, following the principles of content analysis and narrative research. This research contributes theoretically to the studies on celebrity managers and entrepreneurs by bringing a dialogue between studies in the organizational field and cultural studies on celebrities, based on the Brazilian national-regional context. This research contributes to business practice and the training of administrators by addressing that the “fall” and “rise” of celebrity managers and entrepreneurs in national, regional, and physical-virtual spaces have implications not only economic and social but also symbolic-cultural.